Stereological analysis of terminal villi, intervillous space and fibrinoid of adolescent placentas and birth weight of newborns - Sergije Marković; Anis Cerovac; Suad Kunosić; Suada Ramić; Emir Bećirović (Medicinski glasnik, 2019)
Aim: To determine stereological structural parameters of the parenchymal part of the placenta, placental weight and volume of adolescent pregnant women and their correlation with newborns' birth weight. Methods: This prospective study was conducted on a total of 60 human placentas of term pregnancy, divided into two groups according to the age of pregnant women. Experimental group consisted of 30 placentas of pregnant women aged 13-19 years. Control group consisted of 30 placentas of pregnant women aged 20-35 years. Stereological analysis was performed. Results: Volumetric density of terminal villi of adolescent placentas was significantly higher than the one of control group (p <0.0001). The volumetric density of fibrinoid of adolescent placentas was significantly lower than of the control group (p <0.0001). Total volume of terminal villi of adolescent placentas was significantly higher than of the control group (p<0.0001). The total volume of fibrinoid of adolescent placentas was significantly lower than of the control group (p<0.0001). Newborns of adolescent pregnancies had in average lower birth weight of 439.01 g compared to the newborns of the control group (p <0.00001). Conclusion: Adolescent pregnancy affects placental structure, weight and volume. Newborns of adolescent pregnancy have optimal body weight.
Keywords: adolescent pregnancy; histological techniques; maternal-fetal exchange